KARAKTERISTIK MEKANIK PRODUK FIBERBOARD DARI KOMPOSIT SAMPAH PLASTIK (THERMOPLASTIC)-LIMBAH TANDAN KOSONG KELAPA SAWIT (TKKS) - Feris Firdaus; Fajriyanto Fajriyanto (Teknoin, 2006)
The research about thermoplastic wastes-oil palm fiber wastes composites have been conducted. Thermoplastic wastes has become a serious problem in Indonesia, and oil palm fiber wastes also become a serious problems in palm oil industries. The quantity and abundance of the wastes are very much but their utilization is not optimal yet even has no significant added ,economic values. The research was to utilize thermoplastic wastes and oil palm fiber wastes as the main materials to produce fiberboards. The research yields showed that thermoplastic wastes and oil palm fiber wastes composites could be used to produce fiberboards with very satisfied mechanical properties. The mechanical properties of the product were very satisfied even competitive to similar products in markets. The mechanical properties of fiberboards recommended for many kind of materials application, like in building materials and exterior-interior accessories in many appropriate places.Keywords: thermoplastic waste, oil palm fiber waste, composite, fiberboard